Perkembangan Ragam Hias Pada Batu Nisan Tipe Malik As-Shaleh Abad 13 - 17. - libra hari inagurasi (Pusat Penelitian Arkeologi Nasional, 2017)
Decorative variety is a decorative element, its main function as a decoration to beautify the appearance of an object so that it becomes a work of art. The function of the decoration is shown through the integrated forms, textures, materials, and art elements. An object decorated with decorative or decorative elements is a tombstone made of stone. Decorative on the gravestone is formed by sculpting then produce certain forms adorn the headstone so it looks not plain. The development of tombstones of this type and their decorations include the dimensions of time and space. The Malik As-Shaleh type headstone originally evolved from the gravestone on the tomb of Sultan Malik As-shaleh in the 13th century. The tombs spread eastwards to Sumatra, Banten, Lombok, and Gowa in South Sulawesi in the 17th century. The variety of decoration on the gravestone Malik As-Shaleh type in its development is distinguished two groups namely the first group of ornamental fashions whose existence always persists from the beginning to the end of its development and the two groups of decoration whose existence is lost or replaced with other types of decorations. The standard Malik As-Shalh standard headstone is in the tomb of Sultan Malik As-Shaleh. All kinds of decorative elements are on the tombstone so it looks beautiful or highway. The similar type of grave on another tomb has a simple ornamental variety. AbstrakRagam hias merupakan elemen dekoratif, fungsi utamanya sebagai hiasan untuk memperindah penampilan suatu obyek sehingga menjadi sebuah karya seni. Fungsi ragam hias tersebut ditunjukkan melalui bentuk, tekstur, bahan, serta unsur seni yang terpadu. Suatu obyek yang diberi elemen ragam hias atau dekoratif ialah nisan yang dibuat dari bahan batu. Ragam hias pada nisan dibentuk dengan cara dipahat selanjutnya menghasilkan bentuk-bentuk tertentu menghiasi nisan sehingga terlihat tidak polos. Perkembangan batu nisan tipe tersebut beserta ragam hiasnya mencakup dimensi waktu dan ruang. Nisan tipe Malik As-Shaleh pada awalnya berkembang dari nisan pada makam Sultan Malik As-shaleh pada abad ke-13. Selanjunya nisan menyebar ke arah timur ke Sumatra, Banten, Lombok, dan Gowa di Sulawesi Selatan pada abad ke-17. Ragam hias pada nisan tipe Malik As-Shaleh dalam perkembangannya dibedakan dua kelompok yakni pertama kelompok ragam hias yang keberadaannya selalu tetap ada dari awal hingga akhir perkembangannya dan kedua kelompok ragam hias yang keberadaannya hilang atau diganti dengan ragam hias jenis lainnya. Nisan tipe Malik As-Shaleh yang standar terdapat pada makam Sultan Malik As-Shaleh. Semu jenis elemen dekoratif terdapat pada nisan tersebut sehingga terlihat indah atau raya. Adapun nisan tipe sejenis pada makam lainnya memiliki ragam hias yang sederhana.